2003
DOI: 10.1167/iovs.02-0907
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Functional Characterization of a Na+-Independent Large Neutral Amino Acid Transporter, LAT1, in Human and Rabbit Cornea

Abstract: A Na(+)-independent, facilitative transport system, LAT1, was identified and functionally characterized on rabbit cornea. LAT1 was also identified on human cornea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 65 publications
2
22
1
Order By: Relevance
“…[62][63][64] A series of amino acid prodrugs, including alanine-ACV, serine-ACV (SACV), isoleucine-ACV, and g-glutamate-ACV (EACV), were evaluated for in vivo corneal absorption in rabbits. Among these amino acid prodrugs, enhanced stability of SACV resulted in higher area under the curve (AUC), Cmax, and Clast values in comparison to ACV.…”
Section: Prodrugsmentioning
confidence: 99%
“…[62][63][64] A series of amino acid prodrugs, including alanine-ACV, serine-ACV (SACV), isoleucine-ACV, and g-glutamate-ACV (EACV), were evaluated for in vivo corneal absorption in rabbits. Among these amino acid prodrugs, enhanced stability of SACV resulted in higher area under the curve (AUC), Cmax, and Clast values in comparison to ACV.…”
Section: Prodrugsmentioning
confidence: 99%
“…MCT4 together with BASI (Basigin) catalyzes proton-coupled efflux of lactate across the cell membrane [51], and the rapid transport of lactate by MCT/Basigin complex is of critical importance for carbon flux through the later steps of glycolysis [52]. Another two transporters, LAT1 and 4F2, are involved in the transport of large neutral amino acids through the plasma membrane [53][54][55]. And recently a metabolic activation-related Basigin-4F2 complex has been identified on the cell surface that may play a critical role in energy metabolism, probably by coordinating the transport of lactate (via MOT1 and MOT4) and amino acids (via LAT1) [56].…”
Section: Metabolic Proteinsmentioning
confidence: 99%
“…25,26,31 Recently, we reported the expression of a large neutral amino acid transporter on the SIRC cell line as well as on the rabbit cornea and the utility of this cell line in screening for prodrugs targeted toward this transporter. 32,33 These studies, reporting good correlation between uptake by the SIRC cell line and transport across the isolated corneal tissue, suggested that the cell line might serve as a good in vitro model for the rabbit cornea. SIRC is an immortalized cell line and can be propagated several times, as opposed to primary cultures, rendering it more useful as a high-throughput screening tool.…”
Section: Introductionmentioning
confidence: 98%